Informed Decision Making and Abortion: Crisis Pregnancy Centers, Informed Consent, and the First Amendment. Issue 1 (March 2015) - Ahmed, Aziza
<x xml:space="preserve">Abstract</x> Shifting laws and regulations increasingly displace the centrality of women's health concerns in the provision of abortion services. This is exemplified by the growing presence of deceptive Crisis Pregnancy Centers alongside new informed consent laws designed to dissuade women from seeking abortions. Litigation on informed consent is further complicated in the clinical context due to the increased mobilization of facts – such as the gestational age or sonogram of the fetus – delivered with the intent to dissuade women from accessing abortion. In other words, factual information utilized for ideological purpose. To preserve a woman's autonomy and decision‐making capacity, there must be a concerted effort on the part of legislators and courts to place a woman's health at the center of abortion law and policy.